THE ANALYSIS OF THE FACE THREATENING ACT DELIVERED BY ASPERGER SYNDROME IN ADAM MOVIE - Anwar, Achmad Mubasyiril; Anam, Syamsul; Wisasongko, Wisasongko (Publika Budaya, 2013)
When language is communicated within a social context where every interlocutor is expected to carry out a linguistically polite communication which will not bring harm both to him or herself and the person to whom the messages are being delivered, speaker socially should maintain it. This study pragmatic understanding is conducted from a framework based on politeness principle (Brown & Levinson 1987) that aims to explain how face as a universal aspect in politeness study. The research is to find out the pragmatic understanding abilities of Adam, and to understand what utterances for person with Asperger Syndrome is potentially confusing leading him to face threatening act. Qualitative and quantitative research are employed in this study. Qualitative research used is to describe the data in the form of extract conversation and quantitative research is used to know the presentage of the results. The results show Adam tend to use bald on record communication without redressive action toward confusing utterances. Therefore, the prominent weakness Adam has is social interaction and emotional abilities.